1985
DOI: 10.1590/s0074-02761985000100013
|View full text |Cite
|
Sign up to set email alerts
|

Determinacion de las relaciones polimorficas entre Teladorsagia circumcincta (Stadelmann, 1894) y Teladorsagia trifurcata (Ransom, 1907) en condiciones experimentales

Abstract: En el presente estudio se demostró que Teladorsagia circumcincta (Stadelmann, 1894) y T. trifurcata (Ransom, 1907), nemátodes Trichostrongylidae de la sub-família Ostertagiinae, parasitan un espectro de hospedadores similares. La ausencia de barreras reproductivas entre T. trifurcata y T. circumcincta, así como la estabilización rápida de las proporciones de las dos entidades en el seno de la población, evidencia que T. trifurcata es un morfo de T. circumcincta.
It is shown in this study that two species of…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The pairs are in several cases obvious morphs as indicated by experimental data: T. circumcincta and T. trifurcata (see Daskalov, 1974;Lancaster et al, 1983;Morales & Cabaret, 1985); O. ostertagi and O. lyrata (see Lancaster et al, 1983); and O. leptospicularis and O. kolchida (see Lancaster et al, 1983). Drozdz et al (1987), on the basis of natural observations of cervid helminths, suggested that S. boehmi and S. mathevossiani and also S. asymmetrica and S. quadrispiculata are morphs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The pairs are in several cases obvious morphs as indicated by experimental data: T. circumcincta and T. trifurcata (see Daskalov, 1974;Lancaster et al, 1983;Morales & Cabaret, 1985); O. ostertagi and O. lyrata (see Lancaster et al, 1983); and O. leptospicularis and O. kolchida (see Lancaster et al, 1983). Drozdz et al (1987), on the basis of natural observations of cervid helminths, suggested that S. boehmi and S. mathevossiani and also S. asymmetrica and S. quadrispiculata are morphs.…”
Section: Discussionmentioning
confidence: 93%
“…Complete proof of the existence of polymorphic pairs must be determined, however, by experimental intercrosses (Lancaster et al, 1983;Morales & Cabaret, 1985) or critical use of isoenzymes (Nadler, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the common co-occurrence of a dominant (major) and a scarce (minor) species, significant correlation between the intensity of infection of these two species, and regular recovery of monomorphic females, Dróżdż compiled a list of 19 polymorphic species (special combination of major and minor morphs) of the genera Ostertagia , Orloffia , Teladorsagia , Marshallagia and Spiculopteragia . Failure of the genetic isolation of, or experimental hybridization between Teladorsagia circumcincta , T. trifurcata and T. davtiani (Suarez & Cabaret, 1992), and pure infection experiments of lambs with T. circumcincta (Copland, 1965; Morales & Cabaret, 1985) or of calves with Cooperia oncophora (Isenstein, 1971), support the idea that major and minor morphs actually represent a single species. Indeed, male dimorphism or polymorphism of a single species can often be seen in the Ostertagiinae subfamily (Lancaster & Hong, 1981; Lichtenfels & Hoberg, 1993; Lichtenfels et al , 1997).…”
Section: Introductionmentioning
confidence: 87%
“…(Dróżdż et al, 1992). The ratio within a species has a tendency to be constant (Morales and Cabaret, 1995), although some variations have been observed associated with season, geographic area, and host (Dróżdż, 1995;Suárez et al, 1995). In the present study, variation related to the sex and age of the hosts was not observed.…”
Section: Relative Abundance Of Ostertagiinae and Their Male Morphotypesmentioning
confidence: 99%